An Analysis of Character Education Values in English Textbook for Eighth Grade Students Entitled “English for Nusantara” - Mulyadi, Mulyadi; Yukamana, Hanni; Pratiwi, Riska Okta (English Education Study Program, 2025)
This study aimed at describing character education values embedded in the English textbook entitled “English for Nusantara” for eighth grade students in accordance with the Merdeka curriculum. This study was a qualitative study using content analysis method. Data collection techniques used in this study were determine textbook to be included, read, and define the categories, choose which codes to apply for the analysis, compare and establish connections between categories, draw conclusion. The findings showed that the largest number of characters is found in the first dimension in 32 locations in the textbook or 31 percent in total. Second dimension has 15 times to appear or 14.5 percent in total. Third dimension has 12 times to present or 12 percent in total. Fourth dimension has 15 times to show or 14.5 percent in total. Fifth dimension has 19 times to emerge or 18.4 percent in total. At last, sixth dimension has 10 times to come up or 10 percent in total. In summary, the researcher discovers that all of Pancasila student’s profiles that consist of six dimensions are emerged and distributed in all chapters 103 times in book entitled “English for Nusantara” for eight grade students.